Identification of Proteomic Signatures in Chronic Obstructive Pulmonary Disease Emphysematous Phenotype - Bai, Shuang; Ye, Rui; Wang, Cuihong; Sun, Pengbo; Wang, Di; Yue, Yong; Wang, Huiying; Wu, Si; Yu, Miao; Xi, Shuhua; Zhao, Li (Frontiers in Molecular Biosciences, 2021)
Chronic obstructive pulmonary disease (COPD) is a highly heterogeneous disease. Emphysematous phenotype is a type of most common and critical phenotype, which is characterized by progressive lung destruction and poor prognosis. However, the underlying mechanism of this structural damage has not been completely elucidated. A total of 12 patients with COPD emphysematous phenotype (COPD-E) and 9 patients with COPD non-emphysematous phenotype (COPD-NE) were enrolled to determine differences in differential abundant protein (DAP) expression between both groups. Quantitative tandem mass tag-based proteomics was performed on lung tissue samples of all patients. A total of 29 and 15 lung tissue samples from patients in COPD-E and COPD-NE group, respectively, were used as the validation cohort to verify the proteomic analysis results using western blotting. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis were conducted for DAPs. A total of 4,343 proteins were identified, of which 25 were upregulated and 11 were downregulated in COPD-E group. GO and KEGG analyses showed that wound repair and retinol metabolism-related pathways play an essential role in the molecular mechanism of COPD emphysematous phenotype. Three proteins, namely, KRT17, DHRS9, and FMO3 were selected for validation. While KRT17 and DHRS9 were highly expressed in the lung tissue samples of COPD-E group, FMO3 expression was not significantly different between both groups. In conclusion, KRT17 and DHRS9 are highly expressed in the lung tissue of patients with COPD emphysematous phenotype. Therefore, these proteins might involve in wound healing and retinol metabolism in patients with emphysematous phenotype and can be used as phenotype-specific markers.